Development of A Control System for Bitumen Production - Melikov, E.A.; Maharramova, T.M. (Herald of Azerbaijan Engineering Academy, 2025)
The article examines the issues of enhancing the efficiency, safety, and productivity of technological processes in modern industry. In this regard, the effective control of complex chemical and technological processes, such as bitumen production, is not limited to practical experience and operational skills, but also requires the analysis and optimization of these processes using mathematical models. Within the framework of mathematical modeling, as applied to the bitumen production process, the technological sequence of the production under study, the heat and mass transfer processes occurring in one of the main technological apparatuses - the reactor, as well as the control algorithms used, were thoroughly investigated and analyzed in detail. In this regard, the expression of process parameters using mathematical models and their simulation allows for increasing the efficiency and safety of the entire production process. In the course of the research, energy and mass balance equations are formulated, and a dynamic model is developed in the form of differential equations that takes into account heat transfer, material diffusion, and reaction kinetics. The developed mathematical models were simulated in the MATLAB/Simulink environment and analyzed for various operating modes of the process under consideration. A comprehensive analysis of the automated control system used in the bitumen production process was conducted. The main regime parameters: temperature, pressure, flow rate, and level were monitored and regulated in real time, and the relationships between these process parameters were presented in the form of corresponding diagrams.